Targeted gastrointestinal delivery of nutraceuticals with polysaccharide-based coatings - Sampathkumar, Kaarunya (2022)
Oral delivery is one of the facile methods for the administration of active ingredients (AI) like nutraceuticals and drugs. However, its intrinsic disadvantages include poor absorption and bioavailability, degradation of the AI during transit through the gastro-intestinal tract (GIT), and a lack of action specificity. Hence, a delivery system for targeted gastro-intestinal delivery of AI using polysaccharide-based polymers, that are generally recognized as safe (GRAS) and approved for use as a direct food additive, is proposed. In this regard, muco-adhesive chitosan nanoparticles that could adhere to the mucosa of the GIT are fabricated, and encapsulated with AI. These particles are subsequently coated with polysaccharides that have different enzymatic susceptibilities, to allow for specific degradation in the small or large intestines. It is observed that the polysaccharide coating efficiently retarded the non-specific release of the encapsulated agent until it is exposed to its intended environment of release. The cytotoxicity and uptake of chitosan nanoparticles is further evaluated on Caco2 cells. In conclusion, these polysaccharide-coated nanoparticles can potentially be targeted to different organs in the GIT and to be taken up by the enterocytes for improved oral bioavailability.